Six Pillars, Inventory Management & ATF Record-keeping - Ron Ketterling (International Society of Explosives Engineers)
Donna Summer wrote and recorded a song in 1983 with Michael Omartian called, “She Works Hard for the Money.” The song was inspired by her encounter with an exhausted rest room attendant, Onetta Johnson, who is mentioned in the song by name, and featured on the album’s back cover. ISEE President James Daley, in the May/June 2019 in The Journal of Explosives Engineering discussed the Six Pillars related to the ISEE. We will use the Internal Processes pillar to frame this discussion. The Internal Process Pillar includes five separate sub-committees – we will see how this concept applies to both ATF Explosives record-keeping compliance and business process compliance in general. We will discuss electronic and paper record keeping, what works and what doesn’t. We’ll review record keeping in light of those five sub-committees: Audit, Awards, Constitution, Ethics and Planning. You’ll come away with concrete steps you can use to improve your record keeping processes. This paper will show you how to make the hard work of inventory management and ATF record keeping work hard for you.